2007
DOI: 10.1016/j.molcel.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Rad50 Adenylate Kinase Activity Regulates DNA Tethering by Mre11/Rad50 Complexes

Abstract: Mre11 and Rad50 are the catalytic components of a highly conserved DNA repair complex that functions in many aspects of DNA metabolism involving double-strand breaks. The ATPase domains in Rad50 are related to the ABC transporter family of ATPases, previously shown to share structural similarities with adenylate kinases. Here we demonstrate that Mre11/Rad50 complexes from three organisms catalyze the reversible adenylate kinase reaction in vitro. Mutation of the conserved signature motif reduces the adenylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 49 publications
3
118
0
Order By: Relevance
“…We also showed that the unwinding of DNA ends by the MRN complex is essential for the ATM stimulation. This was based on our analysis of the Rad50 S1202R mutant, which is deficient in ATP-dependent DNA unwinding (Moncalian et al, 2004) as well as in adenylate kinase activity (Bhaskara et al, 2007). In agreement with this finding, experiments using Xenopus egg extracts also showed that the wild-type MRN complex restores ATM kinase activity in Mre11-depleted Xenopus extracts but not the MR(S1202R)N-mutant complex (Costanzo et al, 2004).…”
Section: The Role Of the Mrn Complex In Atm Activationsupporting
confidence: 78%
“…We also showed that the unwinding of DNA ends by the MRN complex is essential for the ATM stimulation. This was based on our analysis of the Rad50 S1202R mutant, which is deficient in ATP-dependent DNA unwinding (Moncalian et al, 2004) as well as in adenylate kinase activity (Bhaskara et al, 2007). In agreement with this finding, experiments using Xenopus egg extracts also showed that the wild-type MRN complex restores ATM kinase activity in Mre11-depleted Xenopus extracts but not the MR(S1202R)N-mutant complex (Costanzo et al, 2004).…”
Section: The Role Of the Mrn Complex In Atm Activationsupporting
confidence: 78%
“…3d). We recently showed that Rad50-associated adenylate kinase activity is required for MRN-dependent DNA tethering 32 ; nevertheless, this activity was not inhibited by mirin ( Supplementary Fig. 5 online).…”
Section: Mirin Inhibits the Nuclease Activity Of Mre11mentioning
confidence: 95%
“…Since meiotic DSB are formed in the chromatin loops rather than on the axial elements (Zickler & Kleckner 1999, Blat et al 2002, a role for Rad50 might be to bridge sister chromatids in order to establish a proper architecture of the sisters engaged in the pre-DSB complex (Wiltzius et al 2005). Finally, a recent study reported that a mutation affecting the adenylate kinase activity of Rad50, necessary for DNA tethering, also abolishes the formation of viable spores, but this study did not examine if meiotic DSB are formed or not (Bhaskara et al 2007). …”
Section: Roles Of the Mre11 Complex In Budding Yeast Meiosismentioning
confidence: 92%
“…Upon DNA binding via the globular domain, the intracomplex interaction is prevented and the intermolecular configuration is favoured, which allows DNA tethering (Moreno-Herrero et al 2005). In addition to ATP binding and hydrolysis, the conserved Fsignature motif_ in the C terminal ATPase domain of Rad50 bears an adenylate kinase activity, which is required for efficient tethering between different DNA molecules, independently of DNA binding (Bhaskara et al 2007). All these observations have led to the proposal that this molecular bridging by the Mre11 complex via the Rad50 coiled-coils constitutes the molecular basis of the Mre11 complex_s influence on recombinational DNA repair.…”
Section: Structure and Biochemical Properties Of The Mre11 Complexmentioning
confidence: 99%